Identifying the Micro-relations Underpinning Familiarity Detection in Dynamic Displays Containing Multiple Objects - North, Jamie S.; Hope, Ed; Williams, A. Mark (Frontiers in Psychology, 2017)
We identified the important micro-relations that are perceived when attempting to recognize patterns in stimuli consisting of multiple dynamic objects. Skilled and less-skilled participants were presented with point light display sequences representing dynamic patterns in an invasion sport and were subsequently required to make familiarity based recognition judgments in three different conditions, each of which contained only a select number of features that were present at initial viewing. No differences in recognition accuracy were observed between skilled and less-skilled participants when just objects located in the periphery were presented. Yet, when presented with the relative motions of two centrally located attacking objects only, skilled participants were significantly more accurate than less-skilled participants and their recognition accuracy improved further when a target object was included against which these relative motions could be judged. Skilled participants can perceive and recognize global patterns on the basis of centrally located relational information.